2012
DOI: 10.3390/en5030731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light and Temperature on Fatty Acid Production in Nannochloropsis Salina

Abstract: Accurate prediction of algal biofuel yield will require empirical determination of physiological responses to the environment, particularly light and temperature. One strain of interest, Nannochloropsis salina, was subjected to ranges of light intensity (5-850 μmol m −2 s −1 ) and temperature (13-40 °C) and its exponential growth rate, total fatty acids (TFA) and fatty acid composition were measured. The maximum acclimated growth rate was 1.3 day −1 at 23 °C and 250 μmol m −2 s −1 . Fatty acids were detected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(103 citation statements)
references
References 20 publications
10
87
2
2
Order By: Relevance
“…Nannochloropsis is a promising strain for biofuel production because of its characteristically high lipid content (9,21,32). The model captures growth through carbon uptake, assuming a 50% carbon content (2,33), and includes photosynthetic rate (P c ), respiration rate (rR c ), and biosynthetic energy required for nitrogen uptake ðΨÞ to calculate the growth rate (μ):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nannochloropsis is a promising strain for biofuel production because of its characteristically high lipid content (9,21,32). The model captures growth through carbon uptake, assuming a 50% carbon content (2,33), and includes photosynthetic rate (P c ), respiration rate (rR c ), and biosynthetic energy required for nitrogen uptake ðΨÞ to calculate the growth rate (μ):…”
Section: Methodsmentioning
confidence: 99%
“…The effects of temperature on the current near-term potential lipid productivity were examined further as part of this study. Typical laboratory-based studies regulate temperature to optimum conditions to maximize production or remove it as a variable (32,39). However, temperature control at large-scale represents an economically unfavorable option based on the amount of raw energy required.…”
Section: Methodsmentioning
confidence: 99%
“…Down-regulation of photosynthesis with a reduction in cellular chlorophyll a (Chl a) and in photosynthetic units has been also reported (Fisher et al 1998, Tamburic et al 2014. However, this reduction in photosynthetic activity was not detrimental, since the cell recovered after the light excess corresponding to midday was left behind, finding that the cell size remained constant but filled with accumulation bodies (Fisher et al 1996(Fisher et al , 1998Van Wagenen et al 2012). Similarly, intact cells were also observed in our study after HL conditions, but we did not analyzed accumulation bodies presence.…”
Section: Discussionmentioning
confidence: 93%
“…During the transesterification of algae, Wagenen, et al, [25] reported a sharp increase in total fatty acid containing elevated palmitic and palmitoleic during exponential growth at high light intensity but with low light intensity, an increase in the relative abundance of unsaturated fatty acid was noted. They also noted that fatty acid increased inversely with temperature.…”
Section: Transesterification Mechanismmentioning
confidence: 99%